Implementation of Augmented Reality Shopping in E-Commerce to Increase Customer's Purchase Intention - Diana Diana; Grasiela Angelina; Inigo Hersanta Sutandyo; Jeremy Michael Yuwono; Ivan Sebastian Edbert; Alvina Aulia (Bina Nusantara University, 2023)
E-commerce has grown immensely in the past few years, especially during the Covid-19 pandemic. This condition brings severe conditions. Most traditional business owners must shift and implement e-commerce into their business models. Although e-commerce has many advantages, it also has limitations. The limitation of e-commerce is that it is difficult for customers to visualize the products they will buy in the real world. Most E-commerce applications only allow customers to see images and reviews of the products they want to buy through the screen of their devices. This situation can decrease customer satisfaction if the products they believe do not match the images. This research aims to help solve the limitations of e-commerce applications by implementing Augmented Reality to help customers visualize the products they buy. The researcher developed an Android-based mobile AR application using Unity and the Vuforia engine. After creating our AR application, we surveyed 46 participants to test our AR application. The researcher used Likert Scale with a scale of 4. The result is that almost all participants agreed that AR makes it easier to visualize the product purchased from e-commerce. An average score of 3.6 shows that most participants strongly agree that AR positively influences their decision-making to buy products.